2014
DOI: 10.1016/j.jvs.2014.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and indications for readmission after lower extremity amputation in the American College of Surgeons National Surgical Quality Improvement Program

Abstract: BACKGROUND Postoperative readmission, recently identified as a marker of hospital quality in the Affordable Care Act, is associated with increased morbidity, mortality and healthcare costs, yet data on readmission following lower extremity amputation is limited. We evaluated risk factors for readmission and post-discharge adverse events following lower extremity amputation in the ACS-NSQIP. STUDY DESIGN All patients undergoing transmetatarsal (TMA), below-knee (BKA) or above-knee amputation (AKA) in the 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 17 publications
1
63
0
Order By: Relevance
“…These results highlight the importance of understanding modifiable risk factors of acute care use after SNF discharge in older adults with ESRD in order to identify interventions to curb acute care use in this population. Among members of this cohort, soft tissue infections at the time of SNF admission were strongly associated with acute care use within 30 days of SNF discharge and support the potential importance of efforts to optimize wound management among patients transitioning from SNF to home (21). Although none of the SNF organizational characteristics were associated with early acute care use in our study, prior studies have suggested that direct care hours per patient are associated with resident outcomes (22).…”
Section: Discussionsupporting
confidence: 58%
“…These results highlight the importance of understanding modifiable risk factors of acute care use after SNF discharge in older adults with ESRD in order to identify interventions to curb acute care use in this population. Among members of this cohort, soft tissue infections at the time of SNF admission were strongly associated with acute care use within 30 days of SNF discharge and support the potential importance of efforts to optimize wound management among patients transitioning from SNF to home (21). Although none of the SNF organizational characteristics were associated with early acute care use in our study, prior studies have suggested that direct care hours per patient are associated with resident outcomes (22).…”
Section: Discussionsupporting
confidence: 58%
“…Several authors have reported rates of readmission after individual vascular procedures, such as abdominal aortic aneurysm repair (8%-54%), [14][15][16] amputation (9%-18%), [17][18][19] and lower extremity bypass (12%-49%). 8,9,11,20,21 However, there are conflicting reports regarding readmission rates and reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Though the patient population in this study was comparable in size to others in the literature, the ACS-NSQIP database contained relatively few ATR compared to other conditions it has been used to investigate [22][23][24].…”
Section: Discussionmentioning
confidence: 99%